Modern Tactical Evolution In Football - Mirzakarimova N.I. (Euro Asian Journal Publishing, 2024)
This article provides information about the tactical system in football, and the placement of players on the field. In football, it is shown that if the strength of the players, that is, the attackers and the defenders, are equalized, the game will be interesting. Tactical systems in the game "Three Defenders" or "Magic Square" have proven to be ineffective nowadays. Instead, 1-4-2-4, 1-4- 3-3 and 1-4-4-2 game processes are presented.
Keywords: Football; tactics; system; field